Human Enhancement and the Post-human subject to the test of DH. How digital technologies are transforming us - Domenella, Camilla (Umanistica Digitale, 2023)
This contribution focuses on the role played by digital technologies in transforming the human condition. Digital technologies are presented as a particular form of Human Enhancement already in place, in contrast with the transhumanist positions. Transhumanists trace in GRIN (geno-, robo-, info-, nano-) technologies the conditions for desirable future human enhancement in terms of physical and cognitive performance and capabilities. Analysing the perspectives addressed by the Digital Humanities and taking into account theories on the Post-Human, our purpose is presenting digital technologies as foundational elements of an enhancement already in place, capable of realising the elements of interrelation, synchronicity, hybridisation of the authentic Post-human being.